2005
DOI: 10.1381/096089205774512537
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Subclinical Hypothyroidism in a Morbidly Obese Population and Improvement after Weight Loss Induced by Roux-en-Y Gastric Bypass

Abstract: Our data confirm that severe obesity is associated with increased TSH. The decrease in TSH was independent of BMI, but occurred in all SH patients. A putative effect of weight reduction on the improvement of SH in all patients may be an additional benefit of bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
75
3
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 30 publications
12
75
3
4
Order By: Relevance
“…This observational finding is compatible with the hypothesis that reductions in BMI may enhance effects of and sensitivity to incretin hormones, such as GLP-1. An increased sensitivity after RYGB has also been described for other hormones, i.e., insulin and thyroxin, independent of weight reduction (28,29). Although it could be considered contradictory to the often observed effect that increased hormonal levels leads to desensitization of the corresponding hormonal receptor, as postprandial GLP-1 levels are increased after RYGB, we do speculate that increased sensitivity for GLP-1 may explain our findings in the fasted state.…”
Section: Discussioncontrasting
confidence: 48%
“…This observational finding is compatible with the hypothesis that reductions in BMI may enhance effects of and sensitivity to incretin hormones, such as GLP-1. An increased sensitivity after RYGB has also been described for other hormones, i.e., insulin and thyroxin, independent of weight reduction (28,29). Although it could be considered contradictory to the often observed effect that increased hormonal levels leads to desensitization of the corresponding hormonal receptor, as postprandial GLP-1 levels are increased after RYGB, we do speculate that increased sensitivity for GLP-1 may explain our findings in the fasted state.…”
Section: Discussioncontrasting
confidence: 48%
“…Alagna et al 19 did not find changes in TSH levels 12 months after biliopancreatic diversion, while Chikunguwo et al 55 and Moulin de Moraes et al 56 did (using gastric bypass). All these studies used basal TSH concentration, whereas we used mean 24-h TSH levels to account for pulsatility.…”
Section: Discussionmentioning
confidence: 95%
“…Isolated hyperthyrotropinemia is often observed in patients with morbid obesity, but its pathogenesis remains poorly understood (17,19). Recent evidence showing that lack of female gender prevalence, normal FT 3 /FT 4 ratios, and normalization of serum TSH following weight loss all support the concept that these patients should not be considered as having subclinical hypothyroidism (19,(24)(25)(26). In agreement with this concept, we recently demonstrated that morbidly obese patients with a raised serum TSH have a significantly lower rate of thyroid Ab positivity when compared with TSH-matched normo-weight patients (19).…”
Section: Discussionmentioning
confidence: 99%